The Potency of Akar Laka Plant (Dalbergia parviflora Roxb) In The Pasie Raya Forest Area, Aceh Jaya District - Mirna Tiadi Kombih; Triaty Handayani; Essy Harnelly (Universitas Syiah Kuala, 2024)
Akar laka plant is one of the non-timber forest products (NTFPs) that has promising prospects in trade. For some ethnic communities, the roots of akar laka plants that have been processed into flakes are used as incense used for certain religious worship. Akar laka plant is one type of liana, which is a vine that supports other plants until it reaches the crown of a tree of a certain height akar laka plants also contain resin, a sticky red oil obtained from distilling the roots of akar laka plants. The purpose of this study was to determine the spatial distribution of akar laka plants in the Pasie Raya forest area, Tuwi Peuriya Village, Pasie Raya District, Aceh Jaya Regency and to determine the quantity of akar laka plants found in the Pasie Raya forest area, Tuwi Peuriya Village, Pasie Raya District, Aceh Jaya Regency. The method used in this research is descriptive survey. Akar laka plant sampling uses a plot measuring 10 m x 10 m for adult levels and 5 m x 5 m for sapling levels to determine plot points using a purvosive sampling method. Data collection for the spatial distribution of akar laka plants uses GPS, after the coordinates are obtained, they will be processed using ArcGis 10.3 software. The results of this study found akar laka plants at the adult level 192 individuals and at the sapling level 70 individuals. Akar laka plants in the Pasie Raya forest area of Tuwie Peuriya Village are evenly distributed in each plot. The community around the Pasie Raya forest utilizes the roots of the akar laka plant to increase the community's economy, taking roots from akar laka plants carried out by the community usually in groups consisting of 2-5 people, the surrounding community usually gets 10-15 kg of harvest.